2020
DOI: 10.1111/epi.16432
|View full text |Cite
|
Sign up to set email alerts
|

Audiogenic seizure as a model of sudden death in epilepsy: A comparative study between four inbred mouse strains from early life to adulthood

Abstract: Objective Mouse models of sudden unexpected death in epileptic patients (SUDEP) using audiogenic seizures (AGS) are valuable because death can occur following a sound‐induced seizure in the absence of any pharmacologic or electric component. However, only a few strains of mice are AGS prone, and the vast majority of studies involve DBA/2 or DBA/1 inbred strains. With the goal of characterizing the variation of AGS susceptibility with age, and of offering a larger panel of mice available for AGS studies, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Furthermore, young DBA/1 mice tend to be small (Martin et al . 2020). It was doubtful that 23–30‐day‐old DBA/1 mice would be able to reliably operate running a running wheel.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, young DBA/1 mice tend to be small (Martin et al . 2020). It was doubtful that 23–30‐day‐old DBA/1 mice would be able to reliably operate running a running wheel.…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancy could be attributed to the fact that for most audiogenic seizureinduce death experiments, respiratory activity is assessed by visualization, which could make it difficult to ascertain breathing, or the lack thereof, during convulsions. Another factor could be that tonic seizures in DBA1/2J mice, which are used in the majority of preclinical SUDEP research, almost always produce death, making S-IRA and death coincident with one another (Martin et al, 2020). Considering tonic seizures are associated with apnea in humans (Gastaut et al, 1963;Wyllie, 2015), it is likely that most, if not all, tonic seizures in mouse models produce apnea.…”
Section: Tonic Phase Apnea and Failure Of Breathing Recoverymentioning
confidence: 99%
“…It is unclear whether tonic phase apnea is necessary for postictal apnea and death, as there is no method to selectively prevent the tonic phase from occurring. However, it has been shown that DBA1/2J and 129/SvTer mice die from tonic, but not clonic, seizures (Martin et al, 2020), implying the tonic phase is important and perhaps necessary for seizure-induced death. Thus, determining cellular and molecular underpinnings of both tonic phase apnea and failure of breathing recovery will be important foci for future SUDEP research.…”
Section: Tonic Phase Apnea and Failure Of Breathing Recoverymentioning
confidence: 99%
“…To test for audiogenic seizures mice were taken from their home cage and transferred to a clean test cage where they were allowed to acclimate for ~20 seconds before the onset of the acoustic stimulus. Similar to a method described previously (Martin et al, 2020), a sonicator (Branson 200 ultrasonic cleaner) was used to produce the audiogenic stimulus directly adjacent to the test cage. The stimulus duration lasted for 50 seconds or until the animal had a behavioral seizure.…”
Section: Audiogenic Seizure Testmentioning
confidence: 99%